Respuesta :

[tex] \huge \boxed{\mathbb{QUESTION} \downarrow}[/tex]

2s +9

———

3r ÷ s

(If r = -14 and s = 6)

[tex] \large \boxed{\mathfrak{Answer \: with \:Explanation} \downarrow}[/tex]

[tex] \sf\frac{2s + 9}{3r \div s} \\ [/tex]

Substitute the values of r & s with -14 & 6 respectively.

[tex] \sf\frac { 2 ( 6 ) + 9 } { 3 ( - 14 ) \div ( 6 ) } \\ [/tex]

Multiply 2 and 6 to get 12.

[tex] \sf\frac{12+9}{\frac{3\left(-14\right)}{6}} \\ [/tex]

Add 12 and 9 to get 21.

[tex] \sf\frac{21}{\frac{3\left(-14\right)}{6}} \\ [/tex]

Multiply 3 and -14 to get -42.

[tex] \sf\frac{21}{\frac{-42}{6}} \\ [/tex]

Divide -42 by 6 to get -7.

[tex] \sf\frac{21}{-7} \\ [/tex]

Divide 21 by -7 to get -3.

[tex] = \boxed{ \boxed{\bf \: - 3}}[/tex]

Answer:

25+9

--------

3r÷5

=2×6+9

----------

3×(-14)÷6

=12+9

---------

(-42)÷6

=21

----

-7

=_3